Coumarins by Direct Annulation: β‐Borylacrylates as Ambiphilic C3‐Synthons. Issue 2 (9th November 2020) - Wienhold, Max; Molloy, John J.; Daniliuc, Constantin G.; Gilmour, Ryan
Abstract: Modular β‐borylacrylates have been validated as programmable, ambiphilic C3 ‐synthons in the cascade annulation of 2‐halo‐phenol derivatives to generate structurally and electronically diverse coumarins. Key to this [3+3] disconnection is the BPin unit which serves a dual purpose as both a traceless linker for C(sp 2 )–C(sp 2 ) coupling, and as a chromophore extension to enable inversion of the alkene geometry via selective energy transfer catalysis. Mild isomerisation is a pre‐condition to access 3‐substituted coumarins and provides a handle for divergence. The method is showcased in the synthesis of representative natural products that contain this venerable chemotype. Facile entry into π‐expanded estrone derivatives modified at the A‐ring is disclosed to demonstrate the potential of the method in bioassay development or in drug repurposing. Abstract : Modular β‐borylacrylates are validated as programmable, ambiphilic C3 ‐synthons for the annulation of 2‐halo‐phenol derivatives to generate diverse coumarins. Key to this [3+3] disconnection is the BPin unit which serves a dual purpose as both a traceless linker for C(sp 2 )–C(sp 2 ) coupling, and as a chromophore extension to enable E → Z alkene isomerisation. Inverting alkene geometry is a pre‐condition to access 3‐susbtituted derivatives. This approach capitalises upon the abundance of 2‐halophenols in biology and may facilitate natural product/drug re‐purposing and the development of imaging tools.